2006
DOI: 10.1111/j.1471-4159.2006.03841.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic selection of sox1GFP‐expressing neural precursors removes residual tumorigenic pluripotent stem cells and attenuates tumor formation after transplantation

Abstract: Because of their ability to proliferate and to differentiate into diverse cell types, embryonic stem (ES) cells are a potential source of cells for transplantation therapy of various diseases, including Parkinson's disease. A critical issue for this potential therapy is the elimination of undifferentiated cells that, even in low numbers, could result in teratoma formation in the host brain. We hypothesize that an efficient solution would consist of purifying the desired cell types, such as neural precursors, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 51 publications
4
109
0
Order By: Relevance
“…In transplantations to the brain, selection of Sox1.GFP þ cells and culture prior to transplantation attenuated tumor formation [40]. Here, we found that despite selecting Rax.GFP þ retinal progenitors prior to transplantation, there was still a risk of tumor formation from ESC-derived cultures.…”
Section: Discussionmentioning
confidence: 65%
“…In transplantations to the brain, selection of Sox1.GFP þ cells and culture prior to transplantation attenuated tumor formation [40]. Here, we found that despite selecting Rax.GFP þ retinal progenitors prior to transplantation, there was still a risk of tumor formation from ESC-derived cultures.…”
Section: Discussionmentioning
confidence: 65%
“…8 The expression of p38a-regulated targets is correlated with the onset of RA-induced neuronal differentiation. To determine whether expression levels of these p38a targets were correlated with the establishment of ESderived neurons, we have analyzed their expression profiles in the E14TG2a-derived sox1-targeted GFP ES cells, known to differentiate efficiently in functional neurons expressing b3-TUBULIN/TUJ1 and MAP2 (microtubule-associated protein 2) proteins under RA treatment (Li et al, 10 Ying et al, 30 Chung et al 31 and O Feraud, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has recently been used to generate Purkinje cell progenitors or floor plate cells (28,29). Previously, we purified Sox1 + NPs from differentiating ES cells, but these cell populations inefficiently generated DA neurons (30), possibly due to the nature of mDA NPs as glia-like floor plate cells rather than Sox1 + NPs (4). These findings led us to hypothesize that it is critical to use developmentally appropriate marker(s) to identify and purify functional and authentic subtype-specific NPs.…”
Section: Discussionmentioning
confidence: 99%